2013
DOI: 10.15580/gjms.2013.3.021513463
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and Management Outcome of Upper Gastrointestinal Bleeding in Adult Patients Presenting at Ekiti State University Teaching Hospital, Ado-Ekiti, Nigeria

Abstract: BACKGROUND AND AIM: Upper gastrointestinal bleeding (UGIB) is one of the commonest gastrointestinal emergencies.Endoscopy done within the first 24 hours of bleeding has been shown to be the most reliable means of establishing the source of upper gastrointestinal haemorrhage. This study was carried out to determine the aetiology and management outcome of patients with UGIB presenting at our facility located in Southwest Nigeria. MATERIALS AND METHOD: 67 patients who presented with UGIB and underwent upper gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…It is also a known fact that mucosal lesions heal quickly and generally the time interval between the bleeding episode and endoscopy can influence the endoscopic diagnosis. The male preponderance in patients that presented with UGIB that was observed in this study was similar to studies by Olokoba et al in Ilorin [12] and Ajayi et al in Ekiti [31].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is also a known fact that mucosal lesions heal quickly and generally the time interval between the bleeding episode and endoscopy can influence the endoscopic diagnosis. The male preponderance in patients that presented with UGIB that was observed in this study was similar to studies by Olokoba et al in Ilorin [12] and Ajayi et al in Ekiti [31].…”
Section: Discussionsupporting
confidence: 92%
“…Bleeding was obscured in 19% of patients with UGIB. This figure was much higher compared to other studies [22,31,32].The reasons for this may include late presentation to seek healthcare especially in a low income poor resource settings after onset of symptoms, poor accessibility to endoscopic facilities and personnel, and most patients pay-out-of-pocket to access medical care in Nigeria. It is also a known fact that mucosal lesions heal quickly and generally the time interval between the bleeding episode and endoscopy can influence the endoscopic diagnosis.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, in our study, gastritis accounted for the third-most common cause of UGIB. It should be noted that Ajayi et al reported that gastritis was the most common cause of UGIB in their case study from southwest Nigeria [ 34 ]. Most of our patients were either farmers, artisans or traders.…”
Section: Discussionmentioning
confidence: 99%
“…Upper gastrointestinal bleeding is traditionally defined as bleeding from the gastrointestinal tract that is proximal to the ligament of Treitz [13]. Risk factors include use of NSAIDs, aspirin, alcohol consumption, cigarette smoking, acid peptic disorders and chronic liver disease among others [13][14][15]. Upper gastrointestinal bleeding is a potentially fatal condition with a mortality rate of 6%-13% in the literature despite advances in critical care monitoring and support [16].…”
Section: Discussionmentioning
confidence: 99%